Supplementation of a High-Fat High-Sucrose Diet With Methyl-Donor Nutrients During Pregnancy and Lactation Modulates the Colonic Vitamin D Signaling Pathway in Weaned Rats. (14th June 2022) - Teoh, Chin May; Renteria, Karisa; Cooper, Analynn; Zhu, Jie; Lane, Michelle; Koh, Gar Yee
Abstract: Objectives: Suboptimal vitamin D status is highly prevalent in obese individuals, predisposing them to higher risks for gastrointestinal and immunological dysfunctions. Evidence has shown that maternal methyl-donor nutrient supplementation (MS) can modify DNA methylation status and improve metabolic health in their offspring. Here, we investigated if MS supplementation in an obesogenic diet during pregnancy and lactation can modulate the vitamin D signaling pathway and gut immunity in offspring at weaning. Methods: After mating, 12-week-old female Sprague-Dawley rats were randomly assigned (n = 10/group) to receive control diet (CON), CON supplemented with methyl-donor nutrients (CON-MS), high-fat high-sucrose diet (HFS), or HFS supplemented with methyl-donor nutrients (HFS-MS). Diets were given during gestation and lactation periods. At weaning (21 days), the offspring (n = 6/group/sex) were euthanized. Serum, colonic mucosa, and cecal content were collected for analysis. Results: Serum levels of 25-hydroxycholecalciferol (25D) in weaned pups from CON-MS and HFS-MS dams were 50% greater ( P  < 0.001) than pups born to CON dams but did not differ from pups born to HFS dams. Diets did not affect serum 25D levels in dams. Gene expressions of colonic vitamin D receptor (VDR), and its downstream target, cathelicidin, in pups from HFS-MS dams was 3-fold ( P  < 0.008) and 2.5-fold ( P  < 0.062) lower, respectively, than pups of HFS dams, and did not differ from pups of CON or CON-MS dams. A positive correlation was demonstrated between colonic VDR and the mRNA expressions of colonic pro-inflammatory modulators, TLR4, IL-1β, and IL-6, and the tight junction protein, ZO-1, respectively. Conclusions: Our results support a role for MS in regulating colonic vitamin D signaling in offspring born to HFS dams, independent of maternal vitamin D status. The upregulation of VDR and the production of antimicrobial peptide, cathelicidin, in pups born to HFS dams could be a compensatory mechanism to suppress colonic low-grade inflammation induced by maternal high-fat diet. Further investigation is warranted to delineate the role of MS in vitamin D-mediated immune regulation, and whether an early establishment of vitamin D status is essential for health outcomes in adulthood. Funding Sources: This study is supported by Texas State University startup and indirect cost return funds.